2018
DOI: 10.1111/1440-1681.12922
|View full text |Cite
|
Sign up to set email alerts
|

Excess weight in children and adolescents is associated with altered subendocardial blood supply among girls but not boys

Abstract: Subendocardial viability ratio (SEVR) is a reliable index of myocardial supply-workload balance. This study sought to investigate whether overweight/obese children and adolescents have altered SEVR and to identify which are the associated factors. This cross-sectional study involved 789 individuals. Central haemodynamic was measured by radial applanation tonometry. Diastolic time was shorter (496 ± 122 vs 537 ± 140 ms, P = .014) and diastolic pressure-time index was lower (2681 ± 412 vs 2814 ± 423 mm Hg second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Studies by other groups have also shown that low SEVR correlates with impaired coronary flow reserve in patients with hypertension, type I and type II diabetes, or low cardiorespiratory fitness in central obesity ( 35 , 36 ). SEVR has been investigated in individuals with obesity, and evolving evidence shows that SEVR is altered in children and adolescents with obesity, although the mechanism by which this effect is mediated has not been fully elucidated ( 16 , 37 ). Recent studies showed that SEVR was positively correlated with insulin sensitivity in both obese and lean adolescents, suggesting an important role of SEVR in early cardiovascular risk determination in children and adolescents ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by other groups have also shown that low SEVR correlates with impaired coronary flow reserve in patients with hypertension, type I and type II diabetes, or low cardiorespiratory fitness in central obesity ( 35 , 36 ). SEVR has been investigated in individuals with obesity, and evolving evidence shows that SEVR is altered in children and adolescents with obesity, although the mechanism by which this effect is mediated has not been fully elucidated ( 16 , 37 ). Recent studies showed that SEVR was positively correlated with insulin sensitivity in both obese and lean adolescents, suggesting an important role of SEVR in early cardiovascular risk determination in children and adolescents ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%